Reading Aloud to Increase Parental Engagement in Children Literacy during the Covid-19 Pandemic - Noeris Meiristiani; Rofiudin Rofiudin; Masfuad Edi Santoso; Sakina Sunmut (ASEAN Journal of Empowering Community, 2021)
The parental engagement of the 1st graders of SD Ihsaniyah Gajahmada Tegal in their children’s early literacy phase is still not maximal. Reading has not become an important part of learning activities at home. Therefore, efforts must be made to encourage parents to pay more attention to children's reading interest by being directly involved in children’s reading activities. The reading aloud activity aims to arouse parental awareness and provide skills for parents of the 1st graders of SD Ihsaniyah Gajahmada Tegal to be able to accompany their children in reading books at home as an effort to develop reading interest from an early age. Materials and demonstration of reading aloud were delivered via podcast and broadcast on Youtube due to social restrictions during the Covid-19 pandemic. Then, parents practiced reading aloud to their children at home. This activity was recorded and the video was sent to the service team for feedback and evaluation. Through this activity, parents could spend their time to assist their children in learning, especially reading. Children learned with enthusiasm and had a pleasant book reading experience. In addition, students' interest in reading will grow because they get a pleasant impression from reading aloud with their parents at home.